Cash Transfers and Formal Labor Markets : Evidence from Brazil - Gerard, François; Naritomi, Joana; Silva, Joana (World Bank, Washington, DC, 2021)
Cash transfer programs have expanded widely in developing countries and have been credited for sizable reductions in poverty. However, their potential disincentive effects on beneficiaries’ labor supply have spurred a heated policy debate. This paper studies the impact of a large-scale program Bolsa Familia in Brazil on local labor markets in a context where such concerns could be particularly strong: eligibility is means-tested and the paper focuses on the formal labor market, where earnings are more easily verifiable. Yet, the analysis finds that an expansion of Bolsa Familia increased local formal employment, using variation in the size of the reform across municipalities. The evidence is consistent with multiplier effects of cash transfers in the local economy, which dominate potential negative effects on formal labor supply among beneficiaries.